Adolescent Kidney Outcomes after Extremely Preterm Birth and Neonatal Acute Kidney Injury: There May be More to the Story - Lupo, Ryan; Chang, Emily; Bjornstad, Erica C.; O'Shea, T Michael; Sanderson, Keia R. (American Journal of Perinatology, 2024)
Objective Among children born extremely preterm (EP), the antecedents of chronic kidney disease (CKD), including neonatal acute kidney injury (nAKI), are not well characterized.Study Design This was a retrospective cohort pilot study. Participants (n = 36) were adolescents born before 28 weeks of gestation enrolled at birth into the extremely low gestational age newborn study, between 2002 and 2004, at the University of North Carolina. Participants were stratified by the primary exposure to nAKI, defined using the modified Kidney Disease Improving Global Outcomes nAKI criteria. Baseline serum creatinine (SCr) was defined as the lowest SCr after 48 to 72 postnatal hours. The primary outcome was an abnormal kidney profile during adolescence, defined as having one or more of these outcomes: elevated blood pressure (>120/80 mm Hg), microalbuminuria (urine microalbumin/creatinine >30 µg/g), or an abnormal kidney volume measured by ultrasound (total kidney volume corrected for body surface area <10th%ile for age).Results Half of the participants had a history of nAKI. Thirteen had stage 1 nAKI, four had stage 2, and one had stage 3 nAKI. At 15 years of age, 50% were overweight/obese, 31% had elevated blood pressure (BP), 11% had abnormal kidney volumes, and 17% had microalbuminuria. The relative risk for having an abnormal kidney profile during adolescence among participants with a history of nAKI was 0.63 (95% confidence interval: 0.3–1.3, p = 0.2).Conclusion In this sample of adolescents born EP, a history of nAKI was not associated with elevated BP, microalbuminuria, or abnormal kidney volume. Future studies are needed in larger samples to better characterize the relationship between nAKI and CKD in EP-born children.Key Points
Keywords: acute kidney injury; chronic kidney disease; infants